MGB plan to destroy group of lithuanian emigree - Juodis, Darius (Genocidas ir rezistencija, 2006)
The Soviet security bodies have always been following very closely the Lithuanian emigration, its various societies, and more active figures. The Soviet security structures tried very hard to disorganise and discredit the activities of the Lithuanian diaspora in the eyes of ordinary emigrants and Western authorities. A broad range of information about the life of Lithuanians living abroad was collected on a regular basis. The data obtained was used by the security services to plan and carry out special operations. However, the harsh actions of the chekists, such as the kidnapping of prominent expatriates, pale in comparison to the 1953 plan devised by the MGB to physically destroy many persons hostile to the Soviet system. This plan illustrated a radical attempt to overhaul the situation in the Lithuanian diaspora.